P029 Activation of FXR restores expression of genes dysregulated in human IBD and suppresses TNFa and IL-6 signaling pathways in adoptive transfer colitis model. (27th May 2021) - Liu, X; Milik, A; O'Connell, R; White, J; Wagner, B
Abstract: Background: Farnesoid X receptor (FXR) is a ligand-activated nuclear hormone receptor highly expressed in the gastrointestinal tract. We have shown that FXR agonists improve disease in multiple chronic IBD models (Adoptive transfer (AT) colitis, Mdr1a -/- colitis, and SAMP1/YitFc ileitis) with efficacy similar to anti-IL-12/23. To explore the mechanisms by which FXR agonists reduce colitis in these models and the relevance to human IBD, we identified the genes and pathways regulated by FXR in the AT colitis mice, and compared them with the gene expression profile in human IBD patients. Methods: Colitis was induced by transplanting CD4+CD45RB hi T-cells to C.B-17 SCID mice. Mice were treated with vehicle (n=10), an FXR agonist (p.o. daily, n=10) or anti-IL-12p40 (i.p., weekly, n=5) in therapeutic mode (started 21 days post AT) for 4 weeks. Efficacy was assessed by colon histopathology of inflammation, erosion, gland loss and hyperplasia (0–5 each). RNAseq was performed on colon RNAs (n=5–7 samples/group). Genes differentially regulated by the FXR agonist were compared with published FXR ChIPSeq data (Thomas et al 2010 Hepatology) and a IBD patients' gene expression dataset (GSE73661) to identify FXR target genes associated with human IBD. Gene set enrichment analysis (GSEA) was performed to identify enriched pathways. Results: Direct FXR target genes were identified by comparing genes upregulated by the FXR agonist in the AT mice with FXR ChIPSeq data. Further comparison with GSE73661 identified FXR target genes relevant to human IBD. The majority of these genes are down-regulated in diseased mice and IBD patients compared to healthy controls. Importantly, in GSE73661 dataset, those genes were upregulated in patients that responded to therapy, while remained down-regulated in refractory patients. The function of those genes includes reducing inflammation, improving gut healing and transporter activities. Further pathway analysis by GSEA identified a number of inflammatory pathways significantly upregulated in AT mice and IBD patients, many of which show reduction with the FXR agonist treatment. Of note, TNFα/NF-κB and IL-6/STAT3 pathways, targeted by approved IBD therapies, were significantly elevated in AT mice but reduced by the FXR agonist or anti-IL-12/23. Conclusion: Activation of FXR directly induces IBD-dysregulated genes that can suppress inflammation, promote gut healing and transporter functions. In addition, FXR activation reduced TNFα/NF-κB and IL-6/STAT3 pathways in AT colitis model. These findings support further development of novel FXR agonists as a potential oral therapy for IBD.